(untitled) (Advances in Knowledge Representation, 2025)
Objective: This paper proposes a Solution Concept based on Bitcoin Blockchain to aid in solving the problem of transparency in the Brazilian Real Estate Registry System by registering property payments, property ownership, and property transfers on the Bitcoin Blockchain. Methods: This paper develops the Solution Concept using Unified Modeling Language (UML) diagrams, and it implements the Solution Concept using the Testnet Network of the Bitcoin Blockchain and the Bitcoin Ordinal software utility. Results: Through the Solution Concept, it is verified that there would be more certainty and security in the Brazilian Real Estate Registry System when property payments are made in bitcoin. Additionally, it verifies that provenance and digital thread of property registries would be assured if they were registered on the Bitcoin Blockchain. Conclusions: The Bitcoin Blockchain adds transparency to Brazilian Real Estate Registry System because property payments, property ownership, and property transfers registered on the Bitcoin Blockchain are public, traceable, and immutable (Bitcoin.org, n.d.c).